Relationship between implant stability measurements obtained by two different devices: A systematic review - Andreotti, Agda Marobo [UNESP]; Goiato, Marcelo Coelho [UNESP]; Nobrega, Adhara Smith [UNESP]; Freitas Da Silva, Emily Vivianne [UNESP]; Filho, Humberto Gennari [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Micheline Dos Santos, Daniela [UNESP] (Wiley, 2017)
Background: The aim of this systematic review is to evaluate the relationship between two methods used to assess implant stability, investigating whether both provide similar implant stability assessments for the same clinical case. Methods: A literature search was conducted on MEDLINEPubMed and Scopus databases, without limitation of the publication period, up to November 2015. The following key words were used, with associations among them: dental implant, dental implants, Osstell, resonance frequency analysis, implant stability quotient, ISQ, Periotest, Periotest value, and PTV. Inclusion criteria were English language, prospective, retrospective, and randomized controlled clinical trials that evaluated implant stability through use of resonance frequency analysis (RFA) and damping capacity analysis (DCA). The study should assess implant stability of only a specific region for all patients or discriminate results evaluated for each region if the analysis had been made in various regions; RFA and DCA should have been applied in the same implants and periods. Studies have been carefully selected, and data of interest were tabulated. Results: Six studies met the inclusion criteria. Although there was significant numerical correlation between values obtained by both methods, data showed that less than half (46%) of cases coincided in relation to implant stability classification. Conclusions: It can be considered that there is not always a consensus and standardization in the classification of implant stability related to the values obtained by RFA and DCA devices, which could create disagreements and miscommunication among dentistry professionals.
Keywords: Bone-implant interface; Dental implants; Osseointegration prosthesis implantation; Review